How to produce creative publications : traditional techniques and computer applications - Bivins, Thomas H. (Thomas Harvey), 1947-; Ryan, William E. (Lincolnwood, Ill., USA : NTC Business Books, 1991)
The book is divided into two parts: Part I outlines the elements of publication (all its parts), and contains specific, computer-related information. Part II deals only with the four basic publication formats.
Keywords: Graphic design; Typography; Desktop publishing; Graphic design (Typography); Graphic design (Typography) -- Data processing; Associations, institutions, etc. -- Publishing; Corporations -- Publishing; Desktop publishing